2015
DOI: 10.1128/jcm.03534-14
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Genome Sequencing of Clinical Samples Reveals an Unexpected Heterogeneity of Infections by Chlamydia pecorum

Abstract: bChlamydia pecorum is an important global pathogen of livestock, and it is also a significant threat to the long-term survival of Australia's koala populations. This study employed a culture-independent DNA capture approach to sequence C. pecorum genomes directly from clinical swab samples collected from koalas with chlamydial disease as well as from sheep with arthritis and conjunctivitis. Investigations into single-nucleotide polymorphisms within each of the swab samples revealed that a portion of the reads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 40 publications
5
55
0
Order By: Relevance
“…pCpec seems to be highly distributed in strains, however plasmidless strains are also common, raising questions over its function in disease pathogenesis 26 . Culture-independent genome sequencing of sheep, cattle and koala C. pecorum positive clinical swabs demonstrated that not only could multiple strains infect a single host but that a single anatomical site can harbour multiple C. pecorum strains 27 , somewhat confirming observations from molecular epidemiology but also reiterating complex epidemiology of these infections.…”
Section: Pecorum Molecular Epidemiologysupporting
confidence: 52%
See 1 more Smart Citation
“…pCpec seems to be highly distributed in strains, however plasmidless strains are also common, raising questions over its function in disease pathogenesis 26 . Culture-independent genome sequencing of sheep, cattle and koala C. pecorum positive clinical swabs demonstrated that not only could multiple strains infect a single host but that a single anatomical site can harbour multiple C. pecorum strains 27 , somewhat confirming observations from molecular epidemiology but also reiterating complex epidemiology of these infections.…”
Section: Pecorum Molecular Epidemiologysupporting
confidence: 52%
“…pecorum genome-derived phylogenies highlighted the polyphyletic history of the pathogen itself, and provided important clues about the evolutionary origins of koala strains, giving more confidence to our hypothesis that the origin of C. pecorum infections in Australia is associated with importation of domesticated animals into Australia with European colonisation 3,25,27 .…”
Section: Pecorum Molecular Epidemiologymentioning
confidence: 99%
“…While our group and others have recently used several genome sequencing methods to broaden our knowledge of previously described species in the genus Chlamydia [1317], the current study suggests that a shotgun deep sequencing approach is better suited to novel species. For instance, using “bait” probes designed from a reference genome risks overlooking previously undetected or undescribed features, such as a plasmid [25].…”
Section: Resultsmentioning
confidence: 86%
“…C. pecorum DNA was extracted directly from the host 82 cell contaminants using Sure-Select RNA probes and sequenced using an Illumina Hi-Seq to 83 produce 101bp paired-end reads, as previously described (Bachmann, et al, 2015). These 84 reads were then mapped back to E58 using Bowtie-2 and then variant calling was performed 85 using FreeBayes.…”
Section: Results and Discussion 79mentioning
confidence: 99%
“…Infections frequently contain multiple strains 24 of the same species (Darch, et al, 2015;Taylor, et al, 1995). This has important implications 25 for detecting transmission events (Bachmann, et al, 2015) and determining treatment 26 outcomes (Cohen, et al, 2012). Several methods have been developed to analyse mixed-27 strain populations.…”
Section: Introduction 22mentioning
confidence: 99%